If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + -2p = -83 Solving 17 + -2p = -83 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + -2p = -83 + -17 Combine like terms: 17 + -17 = 0 0 + -2p = -83 + -17 -2p = -83 + -17 Combine like terms: -83 + -17 = -100 -2p = -100 Divide each side by '-2'. p = 50 Simplifying p = 50
| 6n+5=25-4n | | =4x^2-9x^6 | | 10x-10=-4-4x | | 6+91x=52x+30 | | 2a-5=2(a+1)+7a+1 | | x^3-2x+4=0 | | 33+x=40 | | 20-6x=8-10x | | 4(8+9)= | | -19x*7= | | 2(y-6)+16y=10y-70 | | a-19=22 | | 2x+3x=-15+2 | | -19*7= | | 2+8x=-33+x | | sin(69)=y/54 | | 10x+55-20x+30=50 | | 11x-6-4x+1=9-8-2x+12 | | 13x-9y=10 | | -3a^7+(9a^7-9b)= | | 3(x+5)=3(3x+12) | | 7(n-3)+3(n-4)=2 | | (1/3*3.14*2*7)^2 | | 4/3x-3/2x | | 6x-16=8x+2 | | H=-16t^2+62t+5 | | 0.9(5x+10)=1.6-(x+2) | | (1/3(3.14)2(7)^2 | | X+11=6x-7x+5 | | -4(2t-4)+3t=4t-7 | | (1/3(3.14)2(7))^2 | | (-8u-4)+(5u-2)= |